Performance and emissions of spark-ignition engines fuelled with petrol and methane - Karagoz, Yasin; Balci, Ozgun; Gezer, Onur; Koten, Hasan; Isin, Ovun (EMERALD GROUP PUBLISHING LTD, 2021)
Diesel engines using compression ignition are increasingly prohibited in cities due to increased environmental concerns. This could lead to greater use of low-powered spark-ignition (SI) engines in hybrid electrical cars. Using alternative fuels is important for SI engines. In this research study, performance and in-cylinder pressure data were collected from petrol-and methane-fuelled SI engines. A theoretical engine model was then verified using experimental data. The theoretical results for methane and petrol were finally compared for different engine speeds. The theoretical model used a combustion model and a chemical kinetics model to compare the effects of methane and petrol on engine performance and emissions at different engine speeds. Thanks to the high knock resistance of methane, the most suitable ignition advance value was decided for the methane-fuelled simulation by considering the maximum thermal efficiency to limit assumed reductions in indicated thermal efficiency and indicated mean effective pressure compared to previous studies. A slight reduction in nitrous oxides and carbon monoxide emissions was observed when using methane at full load.
Keywords: pollution; energy conservation; environment; NATURAL-GAS; SI ENGINE; DIRECT-INJECTION; LOAD CONDITIONS; HEAT RELEASE; COMBUSTION; HYDROGEN; BLENDS; GASOLINE; CNG; Energy & Fuels